STRATEGI PEMBINAAN KARAKTER MAHASISWA MELALUI MATA KULIAH PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI - Amir Mukminin (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
This article examines various strategies for character building for students through Islamic Religious Education (PAI) courses at State Islamic Religious Colleges (PTKIN). Character building is essential in the modern era full of moral and ethical challenges, where PTKIN has a strategic role in producing a generation of Muslims with strong character. This study uses a qualitative approach with literature study (library research) to identify and analyze effective strategies. The results of the study indicate that character building strategies through PAI courses at PTKIN include the integration of character values ​​in the syllabus and teaching materials, the use of participatory and experiential learning methods, the role of PAI lecturers as role models, the development of character-based teaching modules, and comprehensive evaluations that not only assess cognitive aspects but also affective and psychomotor. The implementation of this strategy is expected to optimize the role of PAI courses as the main locomotive in the formation of religious, moderate, tolerant, and integrity-based student characters.